On the unification of query algebras and their extension to rational tree structures - Schewe, Klaus-Dieter (ACM International Conference Proceeding Series; Vol. 10: Proceedings of the 12th Australasian database conference : Queensland, Australia; 29 Jan.-01 Feb. 2001, 2001)
In order to come to a unification of existing query algebras, especially for object bases, it is necessary to understand the semantic differences between different data models and associated query algebras. It is argued that all existing query algebras can be expressed by the operations provided by an underlying type system plus a single join-operator. This is still true, if rational tree types are allowed and if these are implemented by using object identifiers. The unification exploits the concept of structural recursion.